Data of ice-nucleating particles in precipitation samples from West Texas - Vepuri, Hemanth S K; Rodriguez, Cheyanne A; Georgakopoulos, Dimitrios G; Hume, Dustin; Webb, James; Mayer, Gregory D; Hiranuma, Naruki (PANGAEA, 2021)
Due to a high frequency of storm events, West Texas is an ideal location to study ice-nucleating particles (INPs) in severe precipitation. As INPs impact the formation of ice crystals in clouds and many types of precipitation in general, it is important to characterize properties of INPs in precipitation samples. The study of INPs in precipitation from the West Texas region is especially important to understand whether the high density of cattle in large open-lot livestock facilities has a discernible impact on regional atmospheric INP concentration and composition near the ground and in clouds. Our data provide the estimates of INPs in air as well as 95% confidence intervals derived from 42 precipitation samples in the Texas Panhandle region from June 2018 to July 2019. Both individual and merged data files are provided. The Variables and/or the column names in the merged data file are defined in the README file. Please read it before analyzing the INP data. We also provide other data used for the relevant manuscript figures production (doi:10.5194/acp-21-4503-2021).
Keywords: Cloud Microphysics; Freezing; Ice Nucleating Particle; Metagenomes; mixed-phase clouds; precipitation